Intensified Biobutanol Recovery by using Zeolites with Complementary Selectivity. Issue 14 (5th July 2017) - Van der Perre, Stijn; Gelin, Pierre; Claessens, Benjamin; Martin‐Calvo, Ana; Cousin Saint Remi, Julien; Duerinck, Tim; Baron, Gino V.; Palomino, Miguel; Sánchez, Ledys Y.; Valencia, Susana; Shang, Jin; Singh, Ranjeet; et al.
Abstract: A vapor‐phase adsorptive recovery process is proposed as an alternative way to isolate biobutanol from acetone–butanol–ethanol (ABE) fermentation media, offering several advantages compared to liquid phase separation. The effect of water, which is still present in large quantities in the vapor phase, on the adsorption of the organics could be minimized by using hydrophobic zeolites. Shape‐selective all‐silica zeolites CHA and LTA were prepared and evaluated with single‐component isotherms and breakthrough experiments. These zeolites show opposite selectivities; adsorption of ethanol is favorable on all‐silica CHA, whereas the LTA topology has a clear preference for butanol. The molecular sieving properties of both zeolites allow easy elimination of acetone from the mixture. The molecular interaction mechanisms are studied by density functional theory (DFT) simulations. The effects of mixture composition, humidity and total pressure of the vapor stream on the selectivity and separation behavior are investigated. Desorption profiles are studied to maximize butanol purity and recovery. The combination of LTA with CHA‐type zeolites (Si‐CHA or SAPO‐34) in sequential adsorption columns with alternating adsorption and desorption steps allows butanol to be recovered in unpreceded purity and yield. A butanol purity of 99.7 mol % could be obtained at nearly complete butanol recovery, demonstrating the effectiveness of this technique for biobutanol separation processes. Abstract : What a butanol day ! The production of biobutanol from fermentation solutions is afflicted by high separation costs, owing to the presence of byproducts and a low final concentration. An alternative downstream process for butanol removal from a fermenter's headspace is proposed by using a specific 2‐stage adsorptive method, which couples very high product recovery with extremely high purity.